Born this way or formed this way? Distal personality traits and proximal self-efficacy of Malaysian students and their academic performance - Toh, Seong-Yuen *; Yasmin, Fakhra; Tehseen, Shehnaz *; Poulova, Petra; Syed Arslan, Haider; Andrews, Elizabeth *; Punitha, Sinnappan; Rayhan Zaky, Mahendra (Asia Pacific Academy of Science Pte. Ltd., 2024)
It has been acknowledged that academic performance has important consequences in one’s career, thus, a better understanding of both distal and proximal predictors deserves consideration. Based on social cognitive theory, this study contributes to the limited research investigating the academic performance of university students in Malaysia using the trait model which considers the mediation of self-efficacy (proximal characteristic) in the relationship between student personality (distal trait) and academic performance (outcomes). In a sample of 264 participants, self-efficacy positively relates to academic performance and positively mediated effects of all traits (except neuroticism) on academic performance. Contrary to past research, conscientiousness, extraversion, and agreeableness do not exert direct effects on academic achievement but instead through self-efficacy. Openness to experience turned out to be the strongest predictor pointing to a need for in-depth investigations into this dimension and for more complex model incorporating other proximal attributes in predicting academic performance in future research.